Composição físico-química e análise sensorial de linguiças elaboradas com carne ovina e castanha-de-caju. - Souza, Nahra Oliveira Balbino de (2017)
The objective of this study was to evaluate the effect of inclusion of cashew nuts on a physical-chemical composition and a sensorial quality of the sausage elaborated with a discarded sheep meat. For the elaboration of the sausage, it used from a meat from an adult female of the Santa Inês breed, acquired directly in commercial slaughterhouse. The ingredients used to make the sausage were meat and fat from the sheep, common salt (2%) and 10, 20 and 30% cashew nuts, plus a control treatment (without cashew nut), totaling four treatments. The dough embedded in pork casing. pH, color, moisture, mineral matter, protein, ethereal extract and cholesterol were analyzed; And a sensory analysis by untrained tasters. There was positive linear effect (P = 0.008) of the cashew nut level on the pH value without day of manufacture of the sausages (day 1). There was a linear negative effect (P <0.001) of the batch of cashew nuts on the cholesterol content. There was influence of the level of cashew nut on the attributes aroma, flavor, softness and juiciness, and overall acceptance. An addition of cashew raises the fat content but reduced cholesterol in sheep meat sausages. A 20% addition of cashew nut improves the overall flavor, aroma and acceptance of sheep sausage.